Bilateral Spontaneous Urinoma in a Patient with Primary Hypothyroidism (Journal of Enam Medical College, 2016)
Urinomas are a rare entity involving collection of urine in the perinephric and adjacent spaces resulting from disruption of the urinary collecting system at any level from the calyx to the urethra. Among other causes, blunt trauma to the abdomen is one of the commonest causes. Literature regarding medical causes leading to urinomas is scarce. We report a case of a patient with spontaneous bilateral urinoma with co-incident hypothyroidism.J Enam Med Col 2016; 6(3): 166-168